Iridium porphyrin-catalysed asymmetric carbene insertion into primary N-adjacent C–H bonds with TON over 1000000 - Li, Zong-Rui; Zhan, Kun; Wang, Yi-Jie; Wu, Liang-Liang; Lu, Guo-Lin; Wang, Hao-Yang; Wan, Xiao-Long; Xu, Zhen-Jiang; Low, Kam-Hung; Che, Chi-Ming (Nature communications, 2025)
Selective functionalization of ubiquitous C-H bonds in organic molecules provides a straightforward and efficient approach to construct complex molecules with fewer synthetic steps and high atom economy, thus promoting more sustainable and economical chemical synthesis. A formidable challenge in the field is to increase the turnover numbers (TONs) for catalytic C-H functionalization reactions reported in the literature (generally <10,000) to reasonably high levels to reduce the cost of the reaction. Another challenge is the selective functionalization of less reactive primary C(sp 3 )-H bonds compared to other types of more reactive C-H bonds. We now demonstrate an efficient iridium porphyrin-catalysed asymmetric carbene insertion into primary N-adjacent C(sp 3 )-H bond of N-methyl indoline and N-methyl aniline derivatives. Using chiral iridium porphyrin as a catalyst, chiral β-amino acid derivatives have been obtained with very high yields and excellent ee values (up to 99%), and TONs as high as 84,000 to 1,380,000. The reaction can be readily performed on a 100 g scale while retaining its high efficiency and selectivity. We also show that this iridium catalysis can efficiently access oligomers and polymers of β-amino acid derivatives via stepwise C-H insertion, demonstrating its potential applications in materials science via C-H bond functionalization reactions. A challenge in the selective functionalization of ubiquitous C-H bonds is to increase the turnover numbers (TONs) for catalytic C-H functionalization reactions, and the selective functionalization of less reactive primary C-H bonds. Here, the authors report iridium porphyrin-catalysed asymmetric carbene insertions into primary N-adjacent C–H bonds, with up to 99% ee and product TON > 1000000.